Exchange Server Fundamentals Video Mentor : Exchange Server skills for MCTS and MCITP - Posey, Brien (Pearson Certification, 2009)
"In 15 hours of personal, interactive video mentoring, five-time Microsoft MVP Brien Posey walks you through all the Exchange tasks and concepts you'll need. Posey is singularly well-qualified to present this course: nobody brings more experience, passion, and excitement to Exchange Server. Here, he combines audio instruction, step-by-step screencasts, and more: everything you need to fully understand the tasks you're watching. There's never been a more efficient, cost-effective, compelling Exchange training solution"--Resource description page.